PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT. BCA FINANCE JAKARTA - Moh Sutoro (JMB : Jurnal Manajemen dan Bisnis, 2020)
This study aims to find out, Career development at PT BCA Finance, to find out Employee Performance at PT BCA Finance, to determine the effect of Career Development on Employee Performance at PT BCA Finance Jakarta (Administrative Staff).This study uses a sampling method of nonprobability sampling, namely by accidental sampling technique with a population of 100 using saturated samples, as many as 100 respondents. The analytical method in processing data is validity test, reliability test, simple linear regression analysis, descriptive analysis method, Pearson product moment correlation test, coefficient of determination and hypothesis test (t test).The results of this study show that Career Development has a positive effect on Employee Performance of 0.616 units, if Career Development is increased by one unit it will affect Employee Performance 0.616, this can be seen from the results of the regression equation Y = 18.46 + 0.616X as well as the contribution of Career Development 51.69% while the remaining 48.31% is influenced by other factors. Hypothesis test results show t_count 10,322 greater than t_table 1,661, then H_o is rejected and H_ (a) is accepted, meaning that there is a significant effect between Career Development on PT BCA Finance Employee Performance.